Performance Evaluation of a Centrifugal Pump at the Gunung Pangilun Drinking Water Treatment Installation, Padang Regional Public Water Utility Company - Rama Pranata; Risal Abu; Mukhnizar Mukhnizar (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The availability of clean water is a fundamental need that must be continuously ensured. The Regional Drinking Water Company (Perumda) of Padang City utilizes centrifugal pumps to distribute water from the intake to the reservoir. However, decreased pump performance can lead to an imbalance between water supply capacity and demand. This study aims to analyze the performance of centrifugal pumps at the Gunung Pangilun Water Treatment Unit, particularly in terms of flow capacity, efficiency, and power consumption. The results show that the combined actual discharge of two pumps was 2250 m³/h, which is 24.24% lower than the specified capacity of 2970 m³/h. The average head was 42 meters with a discharge pressure of 4.2 bar. The pump efficiency decreased compared to the design condition due to flow losses and equipment aging factors. It can be concluded that the pump performance is still within an acceptable range but has experienced a decline in capacity and efficiency. Therefore, regular maintenance and system evaluation are required to improve operational performance and energy efficiency.